Oral administration of Lactiplantibacillus plantarum GKK1 ameliorates atopic dermatitis in a mouse model - Lin, Tzu-Chun; Wu, Yu-Chieh; Tsai, You-Shan; Lin, Shih-Wei; Chen, Chin-Chu; Chen, Ming-Ju; Chen, Yen-Po (Frontiers in Microbiology, 2025)
Background/objectivesAtopic dermatitis (AD) is a prevalent chronic skin condition, especially in young children, with rising incidence in developed countries. AD causes repeated scratching, and thus affecting quality of life. This study evaluated the effects and mechanisms of the probiotic Lactiplantibacillus plantarum GKK1 on AD symptoms in mice.MethodsFive-week-old BALB/c mice were divided into four groups (n = 8): control, AD, low-dose GKK1 (107 CFU/day), and high-dose GKK1 (109 CFU/day). GKK1 was intragastrically administered daily for 42 days. AD symptoms, skin histology, serum antibodies, inflammatory cytokine levels, gut microbiota composition, and short-chain fatty acids (SCFAs) in the intestines were assessed.ResultsGKK1 showed improved skin appearance and reduced inflammation in AD mice, with high-dose GKK1 significantly reducing histological inflammation. The GKK1 treatment upregulated splenic interleukin (IL)-2, suppressed IL-4, IL-5 and IL-17 levels and increased intestinal Lactobacillus and Bifidobacterium spp., contributing to higher SCFAs production in intestine.ConclusionOral L. plantarum GKK1 effectively ameliorated AD symptoms and reduced inflammation in mice. Therefore, L. plantarum GKK1 may serve as a potential treatment for AD.